Efecto del encalado en el establecimiento de Leucaena leucocephala en el Norte de Misiones = Effect of liming on the establishment of Leucaena leucocephala in the North of the Misiones - Loto, Mauro; Weber, D.; Colcombet, Luis; González, Paola; Ziegler, Ariana; Rossner, Maria Belen (Facultad de Ciencias Forestales, UNaM. EEA Montecarlo, INTA. Colegio de Ingenieros Forestales de Misiones (Coiform.), 2024)
Leucaena leucocephala is an alternative forage species for subtropical environments, its main attribute is the high protein content at a relatively lower cost. In this work has been evaluated the impact of liming on height and forage production variables during the period of establishment of the crop, no statistically significant differences (p < 0,05) in height or biomass were detected during the first 123 days.